2021
DOI: 10.1155/2021/8818590
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bianchi Type V Holographic Dark Energy Models in General Relativity and Lyra’s Geometry

Abstract: In this paper, we analyze anisotropic and homogeneous Bianchi type V spacetime in the presence of dark matter and holographic dark energy model components in the framework of general relativity and Lyra’s geometry. The solutions of differential equation fields have been obtained by considering two specific cases, namely, the expansion scalar θ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
5
1
0
Order By: Relevance
“…In order to study the anisotropic inflationary phase, we have evaluated the values of some parameters for an anisotropic universe, e.g., expansion scalar (θ), anisotropy parameter (Δ), the shear scalar (σ), and deceleration parameter (q) in both cases. As seen in figures 1(a), (b) (m ≠ n case), and in figures 5(a), (b) (m= n case), the values of the anisotropy parameter (Δ) and the shear scalar (σ) are large at the initial epoch (t → 0) and become negligible at t → ∞ , suggesting that the Universe expands isotropically at later times, which is consistent with the studies of [53][54][55][56][57]. We have shown that in this model the values of the ratio of shear scalar to expansion scalar ( H 0 ( ) s ) lie well within the observed range (52) as predicted in [25].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In order to study the anisotropic inflationary phase, we have evaluated the values of some parameters for an anisotropic universe, e.g., expansion scalar (θ), anisotropy parameter (Δ), the shear scalar (σ), and deceleration parameter (q) in both cases. As seen in figures 1(a), (b) (m ≠ n case), and in figures 5(a), (b) (m= n case), the values of the anisotropy parameter (Δ) and the shear scalar (σ) are large at the initial epoch (t → 0) and become negligible at t → ∞ , suggesting that the Universe expands isotropically at later times, which is consistent with the studies of [53][54][55][56][57]. We have shown that in this model the values of the ratio of shear scalar to expansion scalar ( H 0 ( ) s ) lie well within the observed range (52) as predicted in [25].…”
Section: Discussionsupporting
confidence: 87%
“…Because of this, just like in the m ≠ n case, the parameters Δ, σ are diminishing functions of time, becoming infinite at t → 0 and disappearing at t → ∞ . This implies that, after a considerable amount of time, this model isotropizes the Universe in this case as well, which is similar to the investigations of [53][54][55][56][57].…”
Section: Parameters For Anisotropic Universesupporting
confidence: 85%
See 1 more Smart Citation
“…Negative pressure is associated with DE, causing the accelerated expansion of the universe. This behavior is consistent with the findings of several studies [37,38]. Positive values for 𝑗 and 𝑙 and negative values for 𝑠 represent accelerated expansion [39].…”
Section: Eejp 3 (2023)supporting
confidence: 92%
“…They discovered that an accelerated expansion period isotropizes both the expansion anisotropy and the anisotropy of the fluid. A host of authors have investigated spatially homogeneous and anisotropic DE models both in general relativity and in modified theories of gravitation (See [15], [21], [26], [31]).…”
Section: Introductionmentioning
confidence: 99%